ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH GO PUBLIC (Studi Kasus pada PT. Jasa Marga Tbk.) - Nur Inayah (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study aims to determine the average difference between the financial performance of PT Jasa Marga Tbk before and after go public. Type of research is descriptive research study with case study approach. Analysis of data using a quantitative approach. Variables used consisted of liquidity ratio (current ratio and cash ratio), the solvability ratio (the ratio of total equity to total assets), and the ratio of profitability (ROE and ROI). Object of study is PT. Jasa Marga Tbk periods 2004-2006 and 2008-2010. The results showed that the performance of the company did go public after experiencing a significant increase, but also decreased compared to before going public. This is evident from the ratio of solvability tend to have drastic downs after go public. While liquidity ratios and profitability ratios tended to increase after go public than before go public. Keywords: financial performance, go public, liquidity ratios, solvability ratios, profitability ratios.